PTH-061 Anti-tumour necrosis factor-alfa drug monitoring in paediatric inflammatory bowel disease. (22nd June 2015) - Muhammed, R; Wong, T; Haller, W; Bremner, R; Protheroe, S
Abstract : Introduction: The lack of familiarity with the Commercial assays to measure anti-Tumour Necrosis Factor-alfa (TNF) drug and antibody levels and the cost implication has limited their widespread clinical use. Method: We have done a retrospective analysis of anti TNF-alfa drug monitoring in patients with IBD over 12 months. We have correlated anti-TNF-alfa drug levels with the presence of anti-TNF antibody, concomitant treatment with Azathioprine and the clinical remission status. We have also looked at the cost effectiveness of anti-TNF-alfa drug monitoring. Results: 89 anti TNF drug and antibody levels were done in 47 patients receiving Infliximab in the last twelve months (41 patients had Crohn's disease, 4 had ulcerative colitis and 2 had IBD unclassified). 14 patients (30%) had below therapeutic levels of Infliximab and all were receiving Infliximab 5 mg/Kg dose. 12 of these patients had Crohn's disease and all these 12 patients were on concomitant treatment with Azathioprine. 7 of these patients (58%) had anti-Infliximab antibody positivity. Out of the 12 Crohn's disease patients with low Infliximab levels, 3 were in deep remission with mucosal healing and these three patients were positive for anti-Infliximab antibodies. In these 3 patients treatment with Infliximab was stopped. Of the 12 patients with Crohn's disease and low levels of Infliximab, 9 (75%) were not in clinical remission. 4 of these patients had antibody positivity and dose escalation to 10 mg/kg achieved clinical remission in only one of these patients. 5 Crohn's disease patients who were not in clinical remission with low Infliximab levels and no anti Infliximab antibodies achieved clinical remission with Infliximab dose increase to 10 mg/kg. 4 patients had Infliximab concentrations higher than the therapeutic range and all these patients were on 10mg/kg dose. 15 patients (32%) had anti-Infliximab antibody positivity and all these patients had Crohn's disease. 7 of these patients had low Infliximab levels, 2 had high Infliximab levels (on 10 mg/kg dose) and 6 had Infliximab levels in therapeutic range. 14 of these patients were receiving concomitant Azathioprine. Out of these 15 patients, 9 were in clinical remission. Overall cost savings of about 9000 GBP per year were achieved by Infliximab dose adjustment, even after considering the cost of these investigations and the cost of increased dose of Infliximab in some patients. Conclusion: Anti-TNF-alfa drug level and antibody monitoring are very useful and cost effective in the management of children with inflammatory bowel disease Disclosure of interest: R. Muhammed Grant/ Research Support from: MSD immunology, Abbvie, Tillotts Pharma, Consultant for: Abbvie, Speaker Bureau of: Abbvie, MSD Immunology, T. Wong: None Declared, W. Haller: None Declared, R. Bremner: None Declared, S. Protheroe Consultant for: MSD Immunology, Conflict with: MSD Immunology.